Halogenated Briarane Diterpenes with Acetyl Migration from the Gorgonian Coral Junceella fragilis. Issue 5 (May 2017) - Cheng, Wei; Li, Xiaodan; Yin, Fuling; van Ofwegen, Leen; Lin, Wenhan
Abstract : Chemical examination of the gorgonian coral Junceella fragilis resulted in the isolation of four pairs of acetyl isomers belonging to briarane diterpenoids, including five new compounds. Their structures were determined on the basis of extensive spectroscopic (IR, MS, NMR, and single‐crystal X‐ray diffraction) analysis in association with the chemical conversion. Each pair of isomers featured by dynamical interconversion through as acetyl migration in 1, 2‐diol, which was postulated to be generated under the formation of a cyclic orthoacetate intermediate. All compounds exerted the inhibitory activities against the nitric oxide production in RAW264.7 macrophage cells. Abstract :